High-Performance Twisted Nylon Actuators for Soft Robots - Jin Sun; Shijing Zhang; Jie Deng; Jing Li; Dong Zhou; Dehong Wang; Junkao Liu; Weishan Chen; Yingxiang Liu (Research)
Twisted nylon actuators (TNAs) are widely recognized in soft robotics for their excellent load-to-weight ratio and cost-effectiveness. However, their limitations in deformation and output force restrict their ability to support more advanced applications. Here, we report 3 performance-enhancing strategies inspired by the construction process of chromosome, which are validated through 3 novel types of TNAs. First, we design a dual-level helical structure, demonstrating remarkable improvements in the deformation (60.2% vertically and approximately 100% horizontally) and energy storage capability (launching a miniature basketball to 131 cm in height). Second, we present a parallel-twisted method, where the output force of TNAs reaches 11.0 N, achieving 12.1% contraction under a load of 15 N (10,000 times its weight). Additionally, we construct the dual-level helical structure based on parallel-twisted TNAs, resulting in a 439.7% improvement in load capability. We have adopted TNAs for several applications: (a) two bionic elbows capable of rotating and shooting a miniature basketball over 130 cm; (b) a robot that can rapidly jump over 30 cm; and (c) a soft finger that achieves contracting (15.3% contraction under 2 kg load), precise bending (tracking errors less than 2.0%), and twisting motions. This work presents approaches for fabricating high-performance soft actuators and explores the potential applications of these actuators for driving soft robots with multifunctional capabilities.